The influence of nonlinear terms in mechanical systems having two degrees of freedom - Tinh, Nguyen Duc (Vietnam Journal of Mechanics, 2006)
For many years the higher order stochastic averaging method has been widely used for investigating nonlinear systems subject to white and coloured noises to predict approximately the response of the systems. In the paper the method is further developed for two-degree-of-freedom systems subjected to white noise excitation. Application to Duffing oscillator is considered.